STUDI LITERATUR: EFEKTIVITAS MODEL PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SEKOLAH DASAR - Faiha Taqiya; Melva Zainil; Inggria Kharisma; Annisa Olivia Memosa (STKIP Subang, 2026)
Mathematical problem-solving ability among Indonesian elementary school students remains at a concerning level, as evidenced by Indonesia’s 68th-place ranking out of 81 countries in PISA 2022 and findings from the 2023 National Competency-Based Assessment (ANBK) showing that more than half of elementary students have not reached the minimum competency standard. This situation calls for the implementation of innovative learning models as a solution, one of which is the Problem Based Learning (PBL) model, which places authentic problems at the center of learning and is proven to encourage students to actively construct understanding through contextual inquiry. This study aims to examine the effectiveness of the PBL model in improving mathematical problem-solving skills of elementary school students using a Systematic Literature Review (SLR) approach, encompassing an analysis of 35 selected journal articles published between 2019 and 2026, sourced from Google Scholar, SINTA, Garuda, and university repositories in Indonesia. Findings across the reviewed studies consistently reveal that PBL effectively and significantly improves students’ mathematical problem-solving ability, with an average effect size classified as large (d = 0.81). PBL effectiveness is influenced by four key moderating factors: quality of the problems used, teacher facilitation competency, duration of implementation, and learning group composition. This study recommends the systematic and sustained application of PBL in elementary mathematics instruction as a concrete step toward improving students’ mathematical competence nationally.